CashCard : the Singapore experience. - Ng, Hwee Cheng. (2008)
Singapore officially launched its own CashCard in late November 1996. However, since its launch, acceptance of the CashCard has been lukewarm and many people are still unaware of what a CashCard is and where to purchase one. One of the objectives of this report is therefore to study the current scenario facing Singapore CashCard holders and to find out what type of response it has attracted so far. This report aims to investigate the current users of the CashCard and to look into ways to improve the uses of the CashCard.